The Relationship of Knowledge, Attitudes, and Actions with the Completeness of the Use of Personal Protective Equipment (PPE) in Farmers Insecticide - Gustina Indriati; Jasmi (Jurnal Penelitian Pendidikan IPA, 2022)
The use of pesticides by farmers on plants that are not by established rules and do not use proper Personal Protective Equipment (PPE) can cause various kinds of health complaints to farmers and pollute the environment. The behavior of farmers in the use of self-protective equipment when mushing and spraying pesticides are very important for farmers. The research objective is to determine farmers' knowledge, attitudes, and actions in using self-protective equipment during compounding and spraying pesticides. This type of research is descriptive (descriptive research), primary data is obtained through direct observation using questionnaires, and secondary data is obtained from Wali Nagari. The research population was conducted on all onion farmers with a total sampling technique of 52 samples. Data were analyzed by univariate. The results of the study are known that the level of knowledge of onion farmers in Kanagarian Alahan Panjang is quite good, reaching 67.3%, the attitude of farmers is good, reaching 94.2%, and the actions of farmers towards the use of pesticides and PPE are not good because of the 52 repetitions only 1.9% who have good action and 55.8% who use PPE completely